Proyecto de factibilidad para el establecimiento de un supermercado en la ciudad de Quevedo año 2010 - Litardo Zarsoza, Manuel Saúl (2010)
This project feasibility for implementation of supermarket "Hiperventas" in Quevedo, Canton is done for determining the possibility of creating a new supermarket in the chapel "Malecón", to which you need to analyze and identify the market sector and meet expectations that generates this kind of business. The process of creation of new enterprises is something very carefully, as well as you can see easily handle it, with the same simplicity can be seen it fail and this may be happening to us. There are different levels in the process of maturation of entrepreneurship, depending on the initial profile and commitment of the entrepreneur, both the commitment of the passenger and the methodology used. According to the needs of the population of the sector and the feasibility of implementation of a supermarket, considers possible the establishment of the new local commercial "Hiperventas", corresponding to the Malecon parish, Quevedo, France to meet these needs and in turn provide excellent service to its customers with a range of products of first necessity and quality at an affordable price. To make the project viable is essential to carry out a study of market in the town for the degree of feasibility and viability; for establishing operational, marketing strategies for the creation of this important undertaking. Clearly, identified by the study of market supply and demand, the implementation of the "Hiperventas" supermarket is feasible, since there is a need for the "Malecón" Parish residents to have this type of establishments. In addition it is necessary to establish marketing strategies to improve the image of the supermarket and structuring seductive, promotional plans in order to attract consumers. With all this and analysing the feasibility study, determined that if the supermarket "Hiperventas" in the indicated field implementation is possible.